Head Stabilization Reflex in Patients with Brain Stem Vascular Lesions - Ferah Kızılay; Hülya Güngör; Sibel Özkaynak (Türk Nöroloji Dergisi, 2009)
OBJECTIVE: The head stabilization reflex (HSR) elicited by stimulating the accessory nerve is an oligo-polysynaptic/plurisegmental flexor reflex, which brings the head back to its previous position in response to a variety of sudden head position changes. This reflex was studied in numerous diseases and was inhibited in patients with cerebellar lesions. The present study aimed to investigate how HSR is affected in patients with brain stem vascular lesions. METHODS: The study included 18 patients with brain stem vascular lesions and 18 normal control subjects. Concentric needle electrodes were inserted into the belly of both the sternocleidomastoid muscle and the accessory nerve, and were stimulated separately from the posterior triangle. In all, 8 HSR responses were recorded and mean onset latencies were measured. RESULTS: By stimulating the left accessory nerve in patients with brain stem vascular lesions, contralateral HSR could not be elicited. Similarly, by stimulating the right accessory nerve, contralateral HSR response was elicited only in 3 of the 18 patients. In contrast, stimulation of both the left and right accessory nerves elicited contralateral HSR in all the controls. CONCLUSION: HSR was inhibited in patients with brain stem vascular lesions. This observation shows that the descending pathways in the brain stem facilitate HSR in a similar fashion as the cerebellum was shown to do in a previous study